2020
DOI: 10.1038/s41598-020-62119-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Spectrum of EYS-associated Retinal Disease in a Large Japanese Cohort: Identification of Disease-associated Variants with Relatively High Allele Frequency

Abstract: Yoshitake 19 , Takeshi iwata 19 , Kazushige tsunoda 1 & JeGc study group † Biallelic variants in the EYS gene are a major cause of autosomal recessive inherited retinal disease (IRD), with a high prevalence in the Asian population. The purpose of this study was to identify pathogenic EYS variants, to determine the clinical/genetic spectrum of EYS-associated retinal disease (EYS-RD), and to discover disease-associated variants with relatively high allele frequency (1%-10%) in a nationwide Japanese cohort. Sixty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 39 publications
2
29
0
Order By: Relevance
“…The proband of family SCRP-18 exhibited rod-cone dystrophy symptoms and carried c.2545C>T and c.5802_5803insT. Similarly, Yang et al (2020) reported rod-cone dystrophy patients carrying EYS mutations in a Japanese population (Pagon, 1988). Therefore, different mutations in EYS could cause distinct phenotypes in patients.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The proband of family SCRP-18 exhibited rod-cone dystrophy symptoms and carried c.2545C>T and c.5802_5803insT. Similarly, Yang et al (2020) reported rod-cone dystrophy patients carrying EYS mutations in a Japanese population (Pagon, 1988). Therefore, different mutations in EYS could cause distinct phenotypes in patients.…”
Section: Discussionmentioning
confidence: 97%
“…R etinitis pigmentosa (RP, OMIM# 268000) refers to progressive degeneration of the retina, which exhibits genetic heterogeneity and a complex clinical phenotype (Daiger et al, 2013). Unfortunately, the pathogenesis of RP has not been completely elucidated (Pagon, 1988;Yang et al, 2020). RP is characterized by degeneration of rod cells, cone cells, and retinal pigment epithelial cells and by progressive functional impairment of the outer retina (Hamel, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with a clinical diagnosis of IRD and available whole‐exome sequencing (WES) genetic data were studied between 2008 and 2018. A total of 1,294 subjects from 730 families for whom genotype–phenotype association studies were completed, were surveyed, including 47 families with XLRP and 141 families with sporadic RP (Fujinami et al, 2016; Fujinami et al, 2019; Fujinami‐Yokokawa et al, 2019; Fujinami‐Yokokawa et al, 2020; Kameya et al, 2019; Katagiri et al, 2020; Kondo et al, 2019; Maeda‐Katahira et al, 2019; Mawatari et al, 2019; Mizobuchi et al, 2019; Nakamura et al, 2019; Nakanishi et al, 2016; Pontikos et al, 2020; Xiao Liu et al, 2020; Yang et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The called variants were filtered based on the allele frequencies in the general Japanese population (less than 1%) of the Human Genetic Variation Database (HGVD; http://www.hgvd.genome.med.kyoto-u.ac.jp/). Hypomorphic variants with high allele frequencies (>1%) were analyzed for three particular genes ( EYS, ABCA4 , USH2A ) (Yang et al, 2020). Depth and coverage for the target areas were assessed using the integrative Genomics Viewer (http://www.broadinstitute.org/igv/).…”
Section: Methodsmentioning
confidence: 99%